Pengaruh Kepuasan Konsumen terhadap Brand Image Kopi Cap Bunga Flamboyant (Kajian pada masyarakat Desa Landih, Kecamatan Bangli, Kabupaten Bangli) - WIJAYANTI, NI WAYAN WITRI; SUSRUSA, KETUT BUDI; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Effect of Consumer Satisfaction on Brand Image of Cap Bunga Flamboyant Coffee (A Study in the Village Community of Landih, Bangli District, Bangli Regency) This study aims to determine the magnitude of the effect of consumer satisfaction on a brand image and the magnitude of the effect of customer satisfaction on the strength of brand associations, the uniqueness of brand associations, and the superiority of brand associations on Cap Bunga Flamboyant Coffee in the Landih Village, Bangli District, Bangli Regency. The analytical method used was quantitative-descriptive analysis. Data collection was done by observation, interview, and documentation. Selection of key informants and number of sample determination were done by purposive method. The sample used in this study amounted to 50 samples. The variables in this study were the effect of consumer satisfaction on the brand image of Cap Bunga Flamboyant Coffee with the indicators used were customer values, customer responses, and customer perception using simple linear regression analysis. The results of the analysis of the equation model formed was Y = 0,149 + 0,919X indicating the value of customer satisfaction on the Cap Bunga Flamboyant Coffee gave a positive impression so that placing a strong brand image and brand image of Cap Bunga Flamboyant Coffee would always be remembered, and ultimately consumer opportunities for repurchase the Cap Bunga Flamboyant Coffee brand became very large, which was followed by the strength of the increasingly strong brand association with a value of +0,875, the uniqueness of the brand association which was getting higher with a value of +0,921, and the superiority of the brand association which was getting better with the value of +0,952 assuming ceteris paribus or other factors that affect the brand image of Cap Bunga Flamboyant Coffee to remain constant.